2022
DOI: 10.3390/cancers14030519
|View full text |Cite
|
Sign up to set email alerts
|

Second Cancers in Classical Hodgkin Lymphoma and Diffuse Large B-Cell Lymphoma: A Systematic Review by the Fondazione Italiana Linfomi

Abstract: Background: The increase of lymphoma patient survival led to a modification of the incidence of long-term sequelae, including second malignancies (SM). Several groups have dealt with the incidence of SM, according to the primary treatment; however, a standardized approach for the early detection and screening of SM in the population of lymphoma survivors should be implemented. Methods: A systematic review was conducted by Fondazione Italiana Linfomi (FIL), in order to define the incidence of SM, the impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…A recent group of systematic reviews has been undertaken by researchers from the Fondazione Italiana Linfomi covering a variety of late effects and elements of survivorship. However, their patient population, inclusion criteria, and search strategies are narrower than the prospective review intends [ 31 36 ]. Other reviews that have specifically investigated models of SC have only included a small number of patients diagnosed with a HM alongside other tumour sites [ 37 , 38 ], used less rigorous methodologies [ 8 , 39 ], or need apprising with more recent research [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent group of systematic reviews has been undertaken by researchers from the Fondazione Italiana Linfomi covering a variety of late effects and elements of survivorship. However, their patient population, inclusion criteria, and search strategies are narrower than the prospective review intends [ 31 36 ]. Other reviews that have specifically investigated models of SC have only included a small number of patients diagnosed with a HM alongside other tumour sites [ 37 , 38 ], used less rigorous methodologies [ 8 , 39 ], or need apprising with more recent research [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This issue has gained further attention with a new treatment approach which guarantees a higher probability of curing the disease and, as a consequence, a higher number of patients at risk of SC. In a systematic review, the incidence of SC was found to be higher in cHL and DLBCL patients treated with standard first-line treatment than in the general population, and increased over time [ 6 ]. As expected, the use of intensified regimens and autologous stem cell transplants increased the risk of SC in both patient populations, and was augmented by RT exposure.…”
mentioning
confidence: 99%